Environmental impact assessment within Asset and Property Management: proposal of measurement and monitoring of energy consumption and efficiency indicators through an IWMS - Ruiz Conejo Neyra, Paula Lucía (2021)
Descargue el texto completo en el repositorio institucional del Politecnico di Milano: http://hdl.handle.net/10589/177382